1988
DOI: 10.1111/j.1476-5381.1988.tb10318.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the effects of viprostol in isolated small blood vessels and thoracic aorta of the rat

Abstract: 1 The effects of viprostol, prostaglandin E2 (PGE2) and nitroglycerin were studied in basilar artery, small mesenteric artery and the vein parallel to it as well as thoracic aorta of the rat. 2 In KCl-contracted basilar artery, viprostol produced a concentration-related biphasic response, contraction at concentrations <3 x 10-6 M and relaxation at concentrations >3 x 10-6 M. PGE2 produced a concentration-related contraction while nitroglycerin produced a concentration-related relaxation. 3 In KCI-contracted sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…Although mepacrine and NDGA are relatively non-specific in effect (Griffith et al, 1984), no inhibition was observed. Furthermore, prostaglandin E2 contracts rat endothelium-denuded aorta (Lai et al, 1988) and LTC4, LTD4 and LTE4 also failed to relax this preparation (this study). Haemoglobin and phenidone, inhibitors of EDRF (Griffith et al, 1984;Martin et al, 1985) and gossypol, an inhibitor of EDRF synthesis and/or release (Forstermann et al, 1986) at concentrations known to inhibit EDRF (also confirmed in this study), failed to inhibit relaxation induced by methacholine.…”
Section: Discussionsupporting
confidence: 50%
“…Although mepacrine and NDGA are relatively non-specific in effect (Griffith et al, 1984), no inhibition was observed. Furthermore, prostaglandin E2 contracts rat endothelium-denuded aorta (Lai et al, 1988) and LTC4, LTD4 and LTE4 also failed to relax this preparation (this study). Haemoglobin and phenidone, inhibitors of EDRF (Griffith et al, 1984;Martin et al, 1985) and gossypol, an inhibitor of EDRF synthesis and/or release (Forstermann et al, 1986) at concentrations known to inhibit EDRF (also confirmed in this study), failed to inhibit relaxation induced by methacholine.…”
Section: Discussionsupporting
confidence: 50%